2005
DOI: 10.21273/horttech.15.4.0864
|View full text |Cite
|
Sign up to set email alerts
|

The Organic Farming Movement in Turkey

Abstract: In the past decade, organic production has become a growing segment of the healthy food market. Organic farming is expanding gradually in many countries, and consumption of organic products is gaining a huge importance in the developed countries, such as the U.S., countries in the European Union (EU), Canada, and Japan. The increase of domestic market demand in developed countries and export potential for developing countries has stimulated organic agricultural production. In this report, we briefly ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…It was determined that the different educational status of Olympic boxers also did not affect their preference for organic food, Sayin et al (2005), reported that educational status is an important variable in organic food consumption preferences in his studies and that there are significant differences between educational status and organic food preferences. In the different results obtained in these studies, it is thought that the quality or field differences of the education obtained are effective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was determined that the different educational status of Olympic boxers also did not affect their preference for organic food, Sayin et al (2005), reported that educational status is an important variable in organic food consumption preferences in his studies and that there are significant differences between educational status and organic food preferences. In the different results obtained in these studies, it is thought that the quality or field differences of the education obtained are effective.…”
Section: Discussionmentioning
confidence: 99%
“…05. İnal et al (2005) and Sayin et al (2005), reported that monthly income had an impact on attitudes and awareness levels towards organic foods. It is thought that the difference between these results may be due to some variables such as monthly income, as well as cultural differences and occupational differences.…”
Section: Discussionmentioning
confidence: 99%
“…The European Union (EU) has also experienced tremendous growth in organic fruit production during the past 15 years, with nearly 4000 ha of fruit crops in the total 4.8 million ha under organic management (Willer and Richter, 2004). Support for organic production is greatest in the EU, where the 140,000 organic farms in member states are provided direct and indirect incentives to increase their organic acreage (Sayin et al, 2005). Organic fruit production areas in Switzerland, for example, increased fivefold in the 1990s as a result of new organic methods for pest and disease control, improved management and production practices, increased marketing incentives, and ''green payments'' for organic production by the EU (Weibel, 2001).…”
Section: Organic Fruit Production: the Global Picturementioning
confidence: 99%
“…The profitability of organic apples was twice that of conventional counterparts in 2001 in New Zealand (Walker and McArtney, 2001). Increased demand for organic fruit in the EU has outpaced supply, with many EU states, such as Germany and the United Kingdom, becoming important markets for imported organic products (Sayin et al, 2005). In New Zealand, for example, organic apples exported to the EU in 2006 garnered a 41% premium price over conventional apples.…”
Section: Organic Fruit Production: the Global Picturementioning
confidence: 99%
See 1 more Smart Citation